Effects of UV-B radiation on phenolic accumulation, antioxidant activity and physiological changes in wheat (Triticum aestivum L.) seedlings. (August 2019) - Chen, Zhijie; Ma, Yan; Weng, Yan; Yang, Runqiang; Gu, Zhenxin; Wang, Pei
Abstract: The production of secondary metabolites and the antioxidant defense systems could be activated in response to ultraviolet-B (UV-B). The effects of UV-B radiation on the phenolic content, antioxidant activity, and physiological changes in wheat seedlings were investigated. Results showed that the free, bound and total phenolic contents and antioxidant activities significantly increased in wheat seedlings after UV-B exposure from the third and fourth day. UV-B radiation of 20 μW/cm 2 led to the highest accumulation of phenolics. Total phenolics, DPPH and ABTS values significantly increased by 26.3, 25.1 and 12.0%, respectively, on day 4 as compared to unirradiated wheat seedlings. The highest respiratory rate and phenylalanine ammonia-lyase activity were also observed with the radiation. The increased UV-B radiation intensified the lipid peroxidation in wheat seedlings and changed the activities of antioxidant enzymes involved in the scavenging of reactive oxygen species. The activities of superoxide dismutase, peroxidase and catalase decreased, while the ascorbate peroxidase activity increased with the enhanced UV-B radiation intensity. This study showed that wheat seedlings could be developed as a functional food ingredient after moderate UV-B radiation. Highlights: Phenolic contents increased in wheat seedlings after UV-B radiation. Antioxidant activities increased in wheat seedlings after UV-B radiation. PAL activity was activated with increased UV-B radiation. Increased UV-B radiation intensified lipid peroxidation in wheat seedlings. UV-B radiation significantly changed the activities of antioxidant enzymes.